Plasmaferese na produção de soros hiperimunes Anti-Crotalus durissus terrificus (Laurenti,1768) em eqüínos - Claudio Fonseca de Freitas (1997)
Six equine were hyperimmunized with Crotalus durissus Terrificus venom for four consecutive cycles. At the end of each cycle the horses were individually bled for four consecutive days and seven litres of blood was collected in each bleeding. A total of 28 litres of blood was obtained from each horse at the end of each bleeding procedure. The potency of plasma declined throughout the bleedings but mantained an antibodies titre well above the minimal required. The plasmapheresis technique used in this equines for the production of anticrotalic antivenom sera yelded na increase of 102% in the volume of hyperimmune plasma produced in comparison to the volume obtained by the standard method of only two bleedings without reinfusion of erytrocytes in the donor horse. The technique allowed the collection of larger volumes of plasma without interfering signihcantly in the clinical status of the animals. The results show that plasmapheresis procedure used is highly recommendable for the production of hyperimmune serum.